2012
DOI: 10.1523/jneurosci.5808-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Survival Motor Neuron Affects Plastin 3 Protein Levels Leading to Motor Defects

Abstract: The actin binding protein plastin 3 (PLS3) has been identified as a modifier of the human motoneuron disease spinal muscular atrophy (SMA). SMA is caused by decreased levels of the survival motor neuron protein (SMN) and in its most severe form causes death in infants and young children. To understand the mechanism of PLS3 in SMA, we have analyzed pls3 RNA and protein in zebrafish smn mutants. We show that Pls3 protein levels are severely decreased in smn−/− mutants without a reduction in pls3 mRNA levels. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 64 publications
0
35
0
2
Order By: Relevance
“…Indeed, overexpression of plastin 3 in a zebrafish model of SMA significantly rescues the axonal growth and branching defects caused by smn1 gene depletion ( Oprea et al, 2008 ). Further analysis of smn1 mutant zebrafish reveals that reduced SMN levels lead to decreased plastin 3 protein expression, NMJ defects and aberrant motor function, and these effects can be corrected by plastin 3 overexpression ( Hao et al, 2012 ). More recently, studies in mice have shown that increased expression of plastin 3 delays axonal degeneration and improves NMJ function ( Ackermann et al, 2013 ) as well as ameliorates survival and neuromuscular phenotype ( Kaifer et al, 2017 ), possibly through the modulation of endocytic pathways ( Hosseinibarkooie et al, 2016 ).…”
Section: Identifying Non-smn Targets To Develop Combinatorial Therapementioning
confidence: 99%
“…Indeed, overexpression of plastin 3 in a zebrafish model of SMA significantly rescues the axonal growth and branching defects caused by smn1 gene depletion ( Oprea et al, 2008 ). Further analysis of smn1 mutant zebrafish reveals that reduced SMN levels lead to decreased plastin 3 protein expression, NMJ defects and aberrant motor function, and these effects can be corrected by plastin 3 overexpression ( Hao et al, 2012 ). More recently, studies in mice have shown that increased expression of plastin 3 delays axonal degeneration and improves NMJ function ( Ackermann et al, 2013 ) as well as ameliorates survival and neuromuscular phenotype ( Kaifer et al, 2017 ), possibly through the modulation of endocytic pathways ( Hosseinibarkooie et al, 2016 ).…”
Section: Identifying Non-smn Targets To Develop Combinatorial Therapementioning
confidence: 99%
“…PLS3 is an F-actin-bundling protein, primarily involved in the regulation of the actin cytoskeleton (Delanote et al, 2005). Interestingly, zebrafish SMN mutants display reduced PLS3 protein production, without changes at the transcriptional level (Hao et al, 2012). Importantly, proteins encoded by SMA modifier genes operate within distinct cellular networks, specifically, actin dynamics, endocytosis and mRNA translational control (Dimitriadi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…9). The different efficacies of SBL-154 in the morpholino and genetic models of SMA may indicate that the compound’s therapeutic effect is restricted to motor neurons, since previously reported suppressor strategies that target motor neurons also failed to increase survival [93], [94]. Even increased SMN levels – if restricted to motor neurons – have limited effects on survival of zebrafish and mouse models of SMA [95][98], which is consistent with the emerging view of SMA as multisystem disorder [99], [100].…”
Section: Discussionmentioning
confidence: 99%